Contemporary sources for the fourth crusade - Andrea, Alfred J. (The medieval mediterranean, 2000)
The Registers of Innocent III -- Count Hugh of Saint Pol's report to the West -- The Devestatio Constantinopolitana -- The Anonymous of Soissons -- The Deeds of the Bishops of Halberstadt -- Ralph of Coggeshall: Chronicle -- Alberic of Trois Fontaines: Chronicle